Model Fisik Bangunan Pelindung Pantai - Raudrina, Yessy; Syahputra, Ichsan; Ridha, Muhammad (Jurnal Teknik Sipil Unaya, 2025)
Coastal settlements are areas that are vulnerable to coastal disasters. One of the coastal treatments that is generally carried out is to protect the coastline using beach buildings. It is hoped that the coastal buildings used can break the energy of sea waves and prevent sea water from entering land areas. The use of flume wave instruments is one way to understand the phenomenon of wave generation that allows runoff to occur. This research aims to look at the wave generation process that is generated using wave generator tools contained in the physical flume wave model. Wave generator tools are used to analyze wave height and overtopping that occur before and after protective structures are applied. Waves are generated using a wave generator with 3 speed variations. The speeds used are 0.38 m/s (10 volts), 0.48 m/s (20 volts) and 1.0 m/s (30 volts).